Tackling regional climate change impacts and food security issues : a critical analysis across ASEAN, PIF, and SAARC - Md Saidul Islam (2021)
Climate change and food security issues are multi-faceted and transcend across national boundaries. Therefore, this paper begins with the premise that regional organizations are optimally positioned to address climate change and food security issues while actively engaging global partners to slow down or reverse current trajectories. However, the potential of regional organizations to play a central role in mitigating these vital concerns has not been realized. In this paper, we focus on three regional organizations—the Association of Southeast Asian Nations (ASEAN), the Pacific Islands Forum (PIF), and the South Asian Association for Regional Cooperation (SAARC) and set out to investigate the multifaceted obstacles that impede regional organizations’ ability to effectively cope with these problems. We qualitatively review the efficacy of policies and examine the connections between politico-economic processes that affect the development, cooperation, and execution of regional policies. In doing so, we review regional policies using five key criteria: (i) planning, (ii) implementation, (iii) cooperation, (iv) legal obligation and (v) international contribution. Our findings suggest that regional organizations face fundamental problems in the implementation of extensive policies due to the lack of cooperation and legal obligation between member nation-states that stems from fundamental prioritization of national development agendas over regional cooperation.